Detection of Viral −RNA and +RNA Strands in Enterovirus-Infected Cells and Tissues - Sami Salmikangas; Jutta E. Laiho; Kerttu Kalander; Mira Laajala; Anni Honkimaa; Iryna Shanina; Sami Oikarinen; Marc S. Horwitz; Heikki Hyöty; Varpu Marjomäki (Microorganisms, 2020)
The current methods to study the distribution and dynamics of viral RNA molecules inside infected cells are not ideal, as electron microscopy and immunohistochemistry can only detect mature virions, and quantitative real-time PCR does not reveal localized distribution of RNAs. We demonstrated here the branched DNA in situ hybridization (bDNA ISH) technology to study both the amount and location of the emerging −RNA and +RNA during acute and persistent enterovirus infections. According to our results, the replication of the viral RNA started 2–3 h after infection and the translation shortly after at 3–4 h post-infection. The replication hotspots with newly emerging −RNA were located quite centrally in the cell, while the +RNA production and most likely virion assembly took place in the periphery of the cell. We also discovered that the pace of replication of −RNA and +RNA strands was almost identical, and −RNA was absent during antiviral treatments. ViewRNA ISH with our custom probes also showed a good signal during acute and persistent enterovirus infections in cell and mouse models. Considering these results, along with the established bDNA FISH protocol modified by us, the effects of antiviral drugs and the emergence of enterovirus RNAs in general can be studied more effectively.